The Epoch of Universalism 1769-1989 / l'époque de L'universalisme 1769-1989. - Hofmann, Franck; Messling, Markus (Berlin/Boston : Walter de Gruyter GmbH, 2020)
How can universality be addressed after the necessary epistemic and ethical critique of Western universalism? Building on such concepts as materiality and reparation, narration and translation, the series Beyond Universalism | Partager l'universel seeks to understand how contemporary cultural and social practices are producing a new consciousness of universality - experiences, reflections, and agencies of a shared humanity.
Intro -- Acknowledgements / Remerciements -- Contents / Table des matières -- On the ends of universalism -- Part I: Histories / Première partie: Histoires -- Napoléon a-t-il réveillé le monde arabe? -- Universalisme des Lumières et impérialisme colonial -- Un culte universaliste de la raison? -- Suez 1869: un cosmopolitisme eurocentré? -- Part II: Global Perspectives / Deuxième partie: Mise en perspectives mondiale -- Linguistics and the intellectual challenge of diversity -- Littérature, culture nationale et guerre -- Trans-cultural and trans-temporal translations -- Writing a global history of 1989 -- Part III: Contestations / Troisième partie: Contestations -- Comment le cauchemar traumatique désagrège-t-il l'universalisme européen? -- Réponses antillaises à l'universalisme européen -- Penser contre la mémoire européenne -- Tempo et rythme des révolutions universelles -- Contributors / Contributeurs -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books